PENYULUHAN TENTANG DAMPAK DAN DETEKSI BAHAN PENGAWET KIMIA BERBAHAYA PADA BAHAN MAKANAN - Sri Martini; Dian Kharismadewi; Elfidiah Elfidiah; Kiagus Ahmad Roni; Erna Y uliwati (Politeknik Negeri Sriwijaya, 2021)
The application of inappropriate synthetic chemical preservatives such as borax and formaldehyde on food products endangering human health should get an important attention of government and society as their usage is increasing due to the increasing needs for fulfilling foods which could be stored and consumed in the longer time as well as some economic reasons. Based on this fact, the lecturers of postgraduate program of University of Muhammadiyah Palembang initiated to conduct a community service to solve this problems by explaining the impact and simple detection ways of those prohibited chemical additives as well as explaining the effective, safe and simple ways to preserve foods to public community in decided location in Talang Putri Plaju Palembang. After conducting the activity, it was found that the society members who attended the event experienced an increasing percentage of understanding the impact of chemical preservatives on health, the way to simply detect them and the ways of preparing natural preservation on food.